EFFORTS TO IMPROVE IPAS LEARNING OUTCOMES FOR 6TH GRADE ELEMENTARY STUDENTS USING THE CULTURALLY RESPONSIVE TEACHING (CRT) APPROACH - Zhanni, M. Reza Azwaldi; Maritasari, Donna Boedi; in, Hurun; Rini, Setia; Hakim, Arif Rahman (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
This research was conducted due to problems found in the classroom, namely the low science learning outcomes of the students and the lack of understanding of concepts and the meaning of learning that fosters critical thinking skills, which causes students to be passive during the learning process. This research aims to improve the learning outcomes of 6th-grade students at SD Negeri 3 Sekarteja by implementing the Culturally Responsive Teaching (CRT) approach in science lessons, particularly on the human musculoskeletal system. The subjects of this study were 30 students in the 6th grade at SD Negeri 3 Sekarteja, consisting of 14 male and 16 female students. This research used the Classroom Action Research (CAR) method, conducted in two learning cycles: planning, implementation, observation, and reflection. Data collection techniques were carried out through tests and quantitative data analysis. The study results showed that implementing the Culturally Responsive Teaching (CRT) approach significantly improved students’ learning outcomes on the human musculoskeletal system. In the pre-cycle stage, student learning outcomes reached 53.3%. In Cycle I, there was an increase in student learning outcomes with a classical completeness of 70%. In Cycle II, there was a further increase in student learning outcomes, achieving a classical completeness of 86.7%. It proves that applying the Culturally Responsive Teaching (CRT) approach effectively improves student learning outcomes in science lessons, particularly on the topic of the human musculoskeletal system